Investigation of the effect of impact load on concrete-filled steel tube columns under fire - Ali Golsoorat Pahlaviani; Ali Mohammad Rousta; Peyman Beiranvand (Fracture and Structural Integrity)
Concrete-filled steel tube (CFST) columns are increasingly used in the construction of high-rise buildings which require high strength and large working space especially at lower stories. As compared to reinforced concrete columns, existence of the exterior steel tube not only bears a portion of axial load but also most importantly provides confinement to the infill concrete.with the confinement provided by the steel tube, axial strength of the infill concrete can be largely enhanced.this paper presents the investigation effect of impact load on concrete-filled steel tube columns under fire by numerical simulations using ABAQUS software.the results indicate that the CFST sections with larger confinement factor ξ=1.23 behaved in a very ductile manner under lateral impact. And the sections with smaller confinement factor ξ=0.44  generally behaved in a brittle mechanism.